CULTURAL SHOCK AND PSYCHOLOGICAL ADJUSTMENT OF THAI STUDENT AT ENGLISH DEPARTMENT IN UNIVERSITAS MUHAMMADIYAH MAKASSAR - Isma Dara Samual; Nur Qalbi; Ratu Yulianti Natsir (FKIP Unismuh Makassar, 2022)
This study aims to find out kinds of Culture shock for Thai student of universitas Muhammadiyah Makassar and the obstacles of the psychological adjustment of Thai student. The subject in this study were 3 people of Thai students at English Department in universitas Muhammadiyah Makassar.The research methodology used descriptive qualitative method. The technique of collecting data was interview with 5 questions that talking about cultural shock and psychological adjustment. The findings of this research according to the observation made by the researcher on the 3 informants that on that have been describe previously it is known that cultural shock experienced are daily language factors, social factors, and cultural factors. The obstacle of psychological adjustment of Thai students there are several factors, namely psychal condition, language, culture and environment.